«Текст як конденсатор культурної пам'яті»: інтертекстуальний простір прози Валерія Шевчука - Приліпко, І. (Слово і Час, 2020)
У статті розглянуто показові аспекти інтертексту прози В. Шевчука. Простежено особливості міжтекстової взаємодії доробку письменника на рівні різних форм і типів інтертексту. Особливу увагу
приділено розкриттю специфіки діалогу творів В. Шевчука з претекстами — агіографією, автобіографічною та щоденниковою літературою бароко. The paper considers the demonstrative aspects of intertext in the prose by Valerii Shevchuk
and focuses on the peculiarities of the works’ interaction with the Bible, mythology, and
literature, which takes place at the level of different forms and types of intertext. Particular
attention is paid to revealing the specific ‘dialogue’ of V. Shevchuk’s works with their
pretexts — hagiography, autobiographical and diary’s literature of Baroque. The examples
discussed testify to the depth and ramifications of the intertextual dialogue in the writer’s
prose, reveal the intellectual, philosophical, and elitist nature of his texts. A dialogue with
the Bible, mythology, world and Ukrainian literature in the works by V. Shevchuk unfolds
in the form of open and hidden quotations, allusions, reminiscences. These details aim at
deepening the representation of ideas and themes, forming the subtexts, interpreting images.
The writer creates a new artistic form — metatext — mainly through the reinterpretation
of the pretexts, among which the works of the Baroque period (poetic, autobiographical,
diary genres) and hagiography dominate. Transforming the pretexts at the level of contents,
plot, genre, time and space, narrative, V. Shevchuk expands them with monologues, dialogues,
descriptions, and details. In the process of interpreting prototexts, the writer resorts
to modeling original images, in the context of which he actualizes some worldview points,
reveals important moral, ethical, and philosophical problems. Allowing the perception of
his work as a ‘textual game’, the writer, at the same time, does not reduce the role of intertext
to the level of intellectual play. Intertext becomes a peculiar way of continuing the literary
discourses of the past in a dialogue with them. They become re-read, ‘supplemented’ and
thus brought once again into the continuous process of forming culture.